Relationship between parenting style and children's behavior problems - Alizadeh, Shahla; Abu Talib, Mansor; Abdullah, Rohani; Mansor, Mariani (Canadian Center of Science and Education, 2011)
In the family, parenting style directly impacts children’s behavior and symptoms of behavior. There is ample evidence to support the correlation between parenting style and children’s behavioral problems. However, parenting style and children’s behavioral problems have received little attention and research interest in Iran. Therefore, the current research is deemed necessary and timely. Thus, the major purpose of this current study is to investigate the relationship between parenting style and children’s behavioral problems. Parenting styles (Authoritative, Permissive, and Authoritarian) were assessed by Parent Authority Questioner (PAQ) and children’s behavioral problems (internalizing and externalizing symptoms) were assessed with the Children’s Behavior Checklist (CBCL). Respondents comprised 681 mothers of children in primary school (347girls and 334 boys) who were identified through their children selected by cluster sampling in the Iranian capital of Tehran. The results of the present study indicate that there is a significant correlation between Authoritative and internalizing (r= - .32, p<.001) externalizing (r= - .28, p<.001), Permissive and internalizing (r= .12, p<.001), externalizing (r= .12, p<.001), Authoritarian and internalizing (r= .25, p<.001), externalizing (r= .26, p<.001). In conclusion Authoritative parenting style with high responsiveness and high demanding in parenting behavior has shown to be directly related to less children’s internalizing and externalizing symptoms.